(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
In his novel ‘Jan-Munish’, Ansaruddin has presented a complete picture of the daily life of Jan-Munish, the lowest level of the rural agrarian society of pre-Green revolutionary period. The novel was published in 2018 in paperback by Abhiyan Publishers. This Ninety five page novel is divided into ten chapters. The background of the novel is Manjilpur village. Manjilpur village is located in the lowlands beyond Gadakhali Dam on the bank of Jalangi. A long embankment runs along Manjilpur to Adamponta. This dam protects Manjilpur village from flash floods. But like Ansaruddin’s other novels, the teenage love does not have happy conclusion. On the last day of Aminuddin’s jute harvest, the Gadakhali dam suddenly broke. The team leader of Jan-Munish Gajudafather along with Bahar and his entire team disappeared in the dammed water stream and were never found. This immortality is the destiny of Migrant Agricultural lebour of that era people. Just as disability, disease and old age block people’s way of earning, those who are able-bodied also have to face various calamities and die prematurely. The hunger and death of marginalized people in the society in the era of globalization of the 21st century is the same in the village life which is potrait in this novel of Ansaruddin. As a result, the novel Jan Munish is valuable as a unique expression of the social- reality and life reality of marginal peasant society.